EFEKTIVITAS BIMBINGAN KELOMPOK MENGGUNAKAN TEKNIK STORYTELLING UNTUK MENINGKATKAN EMPATI PADA SISWA SD NEGERI 2 PRINGGAJURANG - M. Zainuddin; Dwi Endrasto Wibowo; Reza Zulaifi; Nurul Iman (INSIGHT: Jurnal Bimbingan Konseling, 2025)
This study aims to examine the effectiveness of group guidance services using storytelling techniques in enhancing the empathy of sixth grade elementary school students in East Lombok. The research employed a quantitative approach with a quasi-experimental design using pre-test and post-test measurements on ten randomly selected participants. The instrument used was an empathy scale covering four dimensions, while the intervention was carried out through story reading and paired retelling activities. Data were analyzed using comparative tests to determine changes in empathy levels after the intervention. The results indicate a significant increase in empathy with an average score improvement of twelve point three. The greatest increase occurred in the perspective taking dimension, followed by empathic concern, imagination, and personal distress. These findings demonstrate that storytelling is an effective guidance strategy for developing students’ ability to understand the feelings of others.